Pendampingan Penyusunan Laporan Keuangan Pada TK Nurul Insan Palembang - Mulyani Rizki (Jurnal Pengabdian Masyarakat Kesosi, 2022)
One of the obligations of lecturers as mandated by Tri Dharma Perguruan Tinggi is to serve the people. To that end, the authors team performs a form of devotion to the community in the form of mentoring the preparation of financial statements on TK Nurul Insan as a partner built in the field of business early childhood education. Difficulties experienced by partners is the preparation of financial reports and transactions not yet tidy. Through a series of mentoring activities undertaken with partners, progress is being made so that the built partners can record the transactions in a neat manner and the preparation of financial statements according to accounting standards.